Hypoxia-induced Acidosis Uncouples the STIM-Orai Calcium Signaling Complex - Salvatore Mancarella; Youjun Wang; Xiaoxiang Deng; Gavin Landesberg; Rosario Scalia; Reynold A. Panettieri; Karthik Mallilankaraman; Xiang D. Tang; Muniswamy Madesh; Donald L. Gill (2011)
The endoplasmic reticulum Ca(2+)-sensing STIM proteins mediate Ca(2+) entry signals by coupling to activate plasma membrane Orai channels. We reveal that STIM-Orai coupling is rapidly blocked by hypoxia and the ensuing decrease in cytosolic pH. In smooth muscle cells or HEK293 cells coexpressing STIM1 and Orai1, acute hypoxic conditions rapidly blocked store-operated Ca(2+) entry and the Orai1-mediated Ca(2+) release-activated Ca(2+) current (I(CRAC)). Hypoxia-induced blockade of Ca(2+) entry and I(CRAC) was reversed by NH(4)(+)-induced cytosolic alkalinization. Hypoxia and acidification both blocked I(CRAC) induced by the short STIM1 Orai-activating region. Although hypoxia induced STIM1 translocation into junctions, it did not dissociate the STIM1-Orai1 complex. However, both hypoxia and cytosolic acidosis rapidly decreased Förster resonance energy transfer (FRET) between STIM1-YFP and Orai1-CFP. Thus, although hypoxia promotes STIM1 junctional accumulation, the ensuing acidification functionally uncouples the STIM1-Orai1 complex providing an important mechanism protecting cells from Ca(2+) overload under hypoxic stress conditions.